The efficacy of somatostatin treatment in bleeding oesophageal varices - Kadir AKSÖZ; Nafi YAZICIOĞLU; Belkıs ÜNSAL; Uğur GÖNENÇ; Ali ERGİN and Günay ÖNDER and Himmet KARACA and Sadun KOŞAY (Turkish Journal of Gastroenterology, 2020)
-